THE RELATIONSHIP BETWEEN KNOWLEDGE AND EDUCATION OF MOM WITH USING CONTRACEPTIVE DEVICES IN SATELIT HEALTH CARE, BANDAR LAMPUNG - Rades, Miranda; Yusran, M; -, Susianti (Majority, 2015)
Abstract Contraception is an attempt to prevent pregnancy. These efforts are temporary and some permanent. Contraceptive use is one of the variables that affect fertility. The use of contraception in urban areas is slightly higher than rural areas is about 63% and 61%, but the use of modern family planning method is hardly different in both urban and rural regions where the respective 57% and 58%. However, there are differences in the variation of the tool or method of contraception used. This study aimed to determine the relationship between knowledge and education of mom with using contraceptives devices in Satelit health centers, Bandar Lampung. This is a descriptive-analytic study with cross-sectional approach. Samples were obtained amounted to 129 people with the relative precision level (d) 0.05. The sampling technique using accidental sampling technique variable knowledge and education using quisioner’s. Majority of the research results obtained mother’s knowledge is sufficient with a percentage of 37.5%, the majority of mothers’ education level is primary education with a percentage of 60.5%, ie elementary/junior high school, the majority of types of contraception used is the injectable contraceptive, ie 27.9%. Then, there was a significant association between mother’s knowledge with the use of contraceptives (p = 0.000) and there was a significant relationship between education level of mom with the use of contraceptives (p = 0.000). From the results of these studies concluded level of knowledge and education of mom have been associated with the use of contraceptives in Satellite health centers, Bandar Lampung. Keywords: contraception, education, knowledge, satellite health centers. Abstrak Kontrasepsi merupakan upaya untuk mencegah terjadinya kehamilan. Upaya ini ada yang bersifat sementara dan ada pula yang bersifat permanen. Penggunaan kontrasepsi merupakan salah satu variabel yang mempengaruhi fertilitas. Pemakaian kontrasepsi di daerah perkotaan sedikit lebih tinggi dari daerah pedesaan yaitu sekitar 63% dan 61%, tetapi pemakaian cara KB modern hampir tidak berbeda baik di wilayah perkotaan maupun di pedesaan dimana masing-masing 57% dan 58%. Namun demikian, terdapat perbedaan dalam variasi alat atau cara KB yang digunakan. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan dan pendidikan ibu terhadap pemakaian alat kontrasepsi di Puskesmas Satelit Kota Bandar Lampung. Penelitian dilakukan dengan metode penelitian deskriptif-analitik dengan pendekatan cross-sectional. Sampel yang diperoleh berjumlah 129 orang dengan tingkat ketepatan relatif (d) sebesar 0,05. Teknik pengambilan sampel dengan menggunakan teknik accidental sampling.variabel pengetahuan dan pendidikan didapatkan dengan menggunakan kuisioner. Diperoleh hasil penelitian mayoritas tingkat pengetahuan ibu adalah cukup dengan persentase sebesar 37,5%, mayoritas tingkat pendidikan ibu adalah pendidikan tingkat dasar dengan persentase sebesar 60,5%, yaitu SD/SMP sederajat, mayoritas jenis alat kontrasepsi yang digunakan adalah alat kontrasepsi suntik, yaitu 27,9%. Kemudian, ada hubungan yang bermakna antara tingkat pengetahuan ibu terhadap pemakaian alat kontrasepsi (p = 0,025) dan ada hubungan yang bermakna antara tingkat pendidikan ibu terhadap pemakaian alat kontrasepsi (p = 0,000). Dari hasil penelitian tersebut disimpulkan tingkat pengetahuan dan pendidikan Ibu memiliki hubungan terhadap pemakaian alat kontrasepsi di Puskesmas Satelit Kota Bandar Lampung. Kata kunci: alat kontrasepsi, pendidikan, pengetahuan, puskesmas satelit.